1990
DOI: 10.1042/bj2720703
|View full text |Cite
|
Sign up to set email alerts
|

Fate of injected glucagon taken up by rat liver in vivo. Degradation of internalized ligand in the endosomal compartment

Abstract: The uptake and processing of glucagon into liver endosomes were studied in vivo by subcellular fractionation. After injection of [[125I]iodo-Tyr10]glucagon and [[125I]iodo-Tyr13]glucagon to rats, the uptake of radioactivity into the liver was maximum at 2 min (6% of the dose/g of tissue). On differential centrifugation, the radioactivity in the homogenate was recovered mainly in the nuclear (N), microsomal (P) and supernatant (S) fractions, with maxima at 5, 10 and 40 min, respectively; recovery of radioactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 41 publications
6
37
0
Order By: Relevance
“…high (glucagon) (16,17), moderate (insulin) (4,30) and low (EGF and prolactin) (31). Using an alternate approach in which hydrolysis was measured by the generation of degradation products from unlabeled peptides, we have confirmed that EGF and insulin hydrolysis, but not glucagon hydrolysis, appears to be limited.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…high (glucagon) (16,17), moderate (insulin) (4,30) and low (EGF and prolactin) (31). Using an alternate approach in which hydrolysis was measured by the generation of degradation products from unlabeled peptides, we have confirmed that EGF and insulin hydrolysis, but not glucagon hydrolysis, appears to be limited.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, we prepared endosomes at 15 min after EGF injection and the intact vesicles were incubated for various times and pH at 37°C in an isotonic buffer mimicking the intracellular milieu (4,16,17) (Fig. 11).…”
Section: Cross-linking Of [ 125 I]egf To a 30-kda Endosomal Binding Pmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Subsequent investigations have implicated endosomal proteases in processing polypeptide hormones such as glucagon [3][4][5][6] and PTH [7], growth factors such as EGF [8], plant and bacterial toxins such as ricin toxin [9,10] and cholera toxin [11]. The conclusion that degradation of internalized ligands occurs or is, at least in part, initiated in endocytic vesicles is based on: (i) the high recovery of internalized ligands in purified endosomes by subcellular fractionation studies, while little association was observed with lysosomes [12]; (ii) the major accumulation of internalized hormones [3,12] and toxins [11] induced by acidotropic agents (i.e.…”
Section: Early Observationsmentioning
confidence: 99%
“…Subsequent investigations have implicated endosomal proteases in processing polypeptide hormones such as glucagon [3][4][5][6] and PTH [7], growth factors such as EGF [8], plant and bacterial toxins such as ricin toxin [9,10] and cholera toxin [11]. The conclusion that degradation of internalized ligands occurs or is, at least in part, initiated in endocytic vesicles is based on: (i) the high recovery of internalized ligands in purified endosomes by subcellular fractionation studies, while little association was observed with lysosomes [12]; (ii) the major accumulation of internalized hormones [3,12] and toxins [11] induced by acidotropic agents (i.e. chloroquine), while effecting a minor accumulation of these ligands in lysosomes; (iii) the extraction from endosomes of polypeptide hormone fragments of insulin [13], glucagon [3,4,6] and EGF [8] using a reverse-phase high performance liquid chromatography procedure corresponding to the in vivo sites of hormone hydrolysis; (iv) the degradation of endosomal ligands in cell-free endosomes incubated at low pH [1,2,4,8,14]; (v) the identification using morphological [15], biochemical [16] and immunological criteria [1,6,17,18] of soluble and membrane-associated endosomal hydrolases; and (vi) the demonstration using iodinated protein ligands and 0014-5793/96/$12.00 © 1996 Federation of European Biochemical Societies.…”
Section: Early Observationsmentioning
confidence: 99%